Histopathological Study of The Effect of Cisplatin on The Ovaries of Females’ Albino Mice - Waheed, Intissar N.; Ameen, Aveen A.M.; Jasim, Unce J.; Ali, Bakhtyar N. (Science Journal of University of Zakho, 2014)
Cisplatin is a chemotherapeutic agent used for treatment of solid tumors and is asserted as an intermediately gonadotoxic agent. The present study was designed to study the cytotoxic effect of cisplatin on the ovaries of females’ albino mice. Twenty adult albino females’ mice (11 weeks old, with 25gm average weight) were randomly divided into two groups. Group (1) injected i.p. 0.025mg cisplatinB.W. as a single dose, group (2) control. Ten females (five from each group) were dissected after 6 days from injection, while the remaining ten females were dissected after 12 days. Then the cytotoxic effect of cisplatin on both ovarian follicles was evaluated by separately counting each follicle in the histological sections, in addition to study their histopathological changes. The results showed that treatment with cisplatin caused a significant decreased number of ovarian follicles compared with control group and this effect was increased with time after administration. The histopathological study revealed that cisplatin caused damaged in both cortical ovarian follicles and medulla layers. These damages included the detachment of tunica albugina from the ovarian tissues; congestion of blood vessels, pyknosis, shrinkage and deforming of the follicular ova; pyknosis of granulosa cells and their detachment from the basement membrane; disorganization of granulosa cells in addition to disruption of their intracellular contacts with oocytes and destruction of theca cells. In conclusion: treatment with single dose of cisplatin caused damage and significant decrease in number of ovarian follicles which may result in females’ infertility.